The Relationship Between Body Mass Index and Waist-to-Hip Ratio on Menstrual Cycle in Female Cadets of Cohort 4, Republic of Indonesia Defense University - Tresnasih Nuraeni; Elies Fitriani; Flora Ekasari; Satria Pratama; Agus Sutarman (The ASEAN Journal of Military and Preventive Medicine, 2025)
Background: Women’s reproductive health may be influenced by anthropometric factors, including body mass index (BMI) and waist-to-hip ratio (WHR). Menstrual-cycle disorders are common in adolescent and young adult women and may be associated with nutritional status, central adiposity, hormonal imbalance, and lifestyle factors. This study aimed to analyze the relationship between BMI and WHR with menstrual cycle patterns among female cadets of Cohort 4 at the Republic of Indonesia Defense University. Methods: This observational analytic study used a quantitative cross-sectional design. Female cadets meeting the inclusion and exclusion criteria were recruited. Anthropometric measurements were performed to calculate BMI and WHR. Menstrual-cycle data were collected using a structured questionnaire and categorized as normal or abnormal. Fisher’s exact test was used to evaluate the relationship between BMI and menstrual cycle and between WHR and menstrual cycle with a significance level of p<0.05. Results: A total of 55 female cadets were included. Most respondents had normal BMI (78.2%), while 60.0% had WHR classified as at risk. Fisher’s exact test showed no significant association between BMI and menstrual cycle (p=0.164), whereas WHR was significantly associated with menstrual cycle pattern (p=0.000). Conclusion: BMI was not significantly associated with the menstrual cycle among female cadets, but WHR showed a significant relationship. Interventions focusing on healthy nutritional status, ideal fat distribution, and physical activity may support reproductive health in female cadets.